Implementation of aquatic exercise in improving v02max of indoor hockey athletes in garut regency - Daffa, Daffa Ahmad Noor Rs; Alam, Alam Hadi Kosasih; Irwan, Irwan Hermawan (Universitas Suryakancana, 2025)
This study aims to determine the effect of aquatic exercise training on increasing VO₂max of indoor hockey athletes in Garut Regency. The research method used is quantitative with a quasi-experimental design using a one-group pretest–posttest design. The study sample consisted of 15 athletes selected using a total sampling technique. The aquatic exercise training program was carried out for 1 month with a frequency of 3 times a week. VO₂max measurements were carried out using the Bleep Test before (pre-test) and after (post-test) training. The results showed that the average value of VO₂max athletes in the pre-test was 42.07 ml/kg/minute, increasing to 45.73 ml/kg/minute in the post-test. In addition, there was an increase in the category of VO₂max athletes from the category of sufficient to good and very good after participating in the training program. Based on the results of the study, it can be concluded that aquatic exercise training can increase VO₂max or aerobic capacity of indoor hockey athletes in Garut Regency. Training in water provides resistance that helps improve muscle work and the cardiovascular system so that the body is more efficient in using oxygen during physical activity.